Influence of the Atmosphere Composition during Malaxation and Storage on the Shelf Life of an Unfiltered Extra Virgin Olive Oil: Preliminary Results. Issue 2 (21st December 2020) - Macaluso, Monica; Taglieri, Isabella; Venturi, Francesca; Sanmartin, Chiara; Bianchi, Alessandro; De Leo, Marinella; Braca, Alessandra; Quartacci, Mike Frank; Zinnai, Angela
Abstract: The nutraceutical and organoleptic quality of the extra virgin olive oil (EVOO) depends on a process that begins with the olive ripening and ends with the packaging and storage. As the EVOO quality decay is mainly induced by the oxidation process, the gaseous composition of the atmosphere during both malaxation and storage can play a key role. Because of that, the aim of this research work is to determine the influence of the gaseous composition of the atmosphere used during malaxation and storage on an unfiltered EVOO shelf life, and to individuate the best "malaxation atmosphere × storage atmosphere" combination to adopt to more effectively slow down the oil quality decay rate during storage. The combined experimental conditions used during malaxation and storage significantly affect the quality decay rate of the EVOO over one year of storage for all the evaluated parameters. In conclusion, the gaseous composition of the atmosphere used during both malaxation and storage deeply affects the shelf life of the unfiltered EVOO as regards its chemical and sensory features, especially when air is used. On the contrary, the best results are obtained when an inert gas (nitrogen or argon) is used during both phases. Practical Applications : The regular consumption of EVOO represents one of the main cornerstones of the Mediterranean diet. According to the FDA (Food and Drug Administration), this product can be considered as a healthy food because of its extraordinary nutraceutical and organoleptic properties, so that if consumers consume half a tablespoon of olive oil per day—without increasing their daily calorie intake—they can significantly reduce the incidence of several degenerative diseases as well as the risks associated with them. The knowledge of the impact of different "malaxation atmosphere × storage atmosphere" combinations on the quality decay rate during storage of an unfiltered EVOO can allow to identify the best operating conditions to be used during its production and storage, in order to preserve the nutraceutical and organoleptic properties of this product over time, thus extending its commercial life in terms of both quality parameters and healthy properties. Abstract : The aim of this research is to evaluate the role played by the malaxation atmosphere on the EVOO shelf life as a function of the storage atmosphere and consequently to individuate the best "malaxation atmosphere × storage atmosphere" combination in order to preserve the nutraceutical and organoleptic properties of this product over time.